Documenting traditional knowledge in relation to climate change and its effects in Tr'ondëk Hwëch'in traditional territory ... - Winton, Alexandra; Neufeld, David; Neufeld, Erin; McLeod, Georgette; Olson, Jackie; Friendship, Katelyn; Roburn, Shirley; Parsons, Sue; Hume, Trish (Borealis, 2012)
Tr'ondëk Hwëch'in is a self-governing First Nation that signed a Final Agreement with the Yukon Government and Canada in 1998. Tr'ondëk Hwëch'in offers a variety of year-round programming to the community of Dawson City, Yukon and many of these programs are supported by information collected through oral history interviews and the documentation of traditional knowledge. Our IPY project involved multiple phases, including field research, oral history interviews, community mapping, and academic partnerships. Other important aspects of this project included training for youth, and increasing local awareness about climate change. Over a period of nearly two years, the Tr'ondëk Hwëch'in Heritage Department conducted over forty oral history interviews with traditional and local knowledge holders within the communities of Dawson City, Yukon; Fort McPherson, Northwest Territories; and Eagle, Alaska. We incorporated climate change education into our culture camps and regular heritage programming, and developed ... : Type: Research Program: Notes: IPY-Traditional Knowledge in Tr'ondek Hwech'in This metadata record corresponds to an IPY project. Studies completed under this research project are identified as related materials. These studies can also be retrieved using the Polar Data Catalogue.; ...